STRUCTURE OF ISOLATED PRECISION FACTORS OF THE MALE VOLLEYBALL PLAYERS - Aleksandra Vujmilović; Tamara Karalić; Nenad Marelić (University of Banja Luka, Faculty of physical education and sport, 2012)
The subject of this research project is precision as a factor of success of the male volleyball players. The issue relates to the realization of the said motor skills through a clearly defined and valid metric tests typical for the area of technical - tactical structure of volleyball. The aim of the study was to determine the factorial structure of motor abilities of precision for male volleyball players. The task was to determine the correlation between motor tasks with the main components defined as potential factors of the research area. The sample consisted of 40 male volleyball players, members of volleyball teams from Niš (SRB), 14-16 years of age. Eleven motor tests were used to assess the following potential factors: the precision of shooting targets in the horizontal plane, the precision of shooting targets in the vertical plane, body coordination at the volleyball court, the precision of spike technique and nerve-muscle reactions.It was found that there are certain manifest dimensions within the subjects area defined as the area of precision. Then, in the structure of this area of volleyball, acting as precision factors in shooting targets with fingers and "bump" in the horizontal and vertical plane, also confirmed that the coordination of work and factor in the space of volleyball court and a velocity factor of nerve-muscle response.In general it is concluded that within the structure of technical-tactical elements operates particular type of precision in volleyball, that can be defined as factors of precision in the technique of adding a ball with fingers, forearm pass technique ("bump") and spike technique.